Catalyst-Free Photodriven Reduction of α-Haloketones with Hantzsch Ester - Lu, Zheng; Yang, Yong-Qing (Synthesis, 2019)
Catalyst-free dehalogenation of α-haloketones under visible light irradiation is studied. The reactions were carried out in common organic solvent. The outcomes of dechlorination are excellent in yields up to 92%, and it is also applicable to bromides, which give even higher yields. The reaction is tolerable to a broad spectrum of substrates, especially to aromatic ketones, including various aryl and hetaryl groups. There are two examples of aliphatic ketones presented in the paper, although their reactivities are not as high as that of the aromatic ketones.
Keywords: Hantzsch ester; catalyst-free; visible light; dehalogenation; environment-benign